Online teaching at its best : merging instructional design with teaching and learning research - Nilson, Linda Burzotta; Goodson, Ludwika A., 1947- (Jossey-Bass, a Wiley imprint, 2021)
"According to recent research, over 30 states offer fully online school and 26 states offer state online high schools. The number of online course offerings is expected to rise as a result of COVID-19. Even before COVID-19 entered the North American lexicon, a survey of 398 school administrators and 1,500 students conducted by BestColleges found that online programs continued to be high demand. As online teaching stands now, faculty often fail to apply teaching research and theory in designing their online courses. One obstacle is the cognitive load of dealing with online technologies. Another is the absence of pedagogy in most online course design standards. The most important one may lie in the books and articles about how to teach online. Many of them are written for technologists and instructional designers and pay little or no attention to online teaching and learning. Unfortunately, these do not equip faculty with a coherent picture of high-quality online teaching"--Publisher's description.